2009
DOI: 10.4172/1747-0862.1000038
|View full text |Cite
|
Sign up to set email alerts
|

Heterosubtypic anti-avian H5N1 influenza antibodies in intravenous immunoglobulins from globally separate populations protect against H5N1 infection in cell culture

Abstract: With antigenically novel epidemic and pandemic influenza strains persistently on the horizon it is of fundamental importance that we understand whether heterosubtypic antibodies gained from exposures to circulating human influenzas exist and can protect against emerging novel strains. Our studies of IVIG obtained from an infection-naive population (Australian) enabled us to reveal heterosubtypic influenza antibodies that cross react with H5N1. We now expand those findings for an Australian donor population to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Antibody landscapes showed clear agerelated differences among three age groups both pre-and post-vaccination, a phenomenon that was also described by others (6,8,9). Previous studies also showed that antibodies to a novel HA(s) in unexposed populations can increase with age and may vary by geographical location (8,9,13,15,(22)(23)(24)(25)(26)(27)(28). As expected, because adults are exposed to more seasonal influenza viruses and/or vaccines than young children, they have more complex antibody landscapes from past exposures through infection(s) and/or vaccination(s) with multiple influenza viruses (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Antibody landscapes showed clear agerelated differences among three age groups both pre-and post-vaccination, a phenomenon that was also described by others (6,8,9). Previous studies also showed that antibodies to a novel HA(s) in unexposed populations can increase with age and may vary by geographical location (8,9,13,15,(22)(23)(24)(25)(26)(27)(28). As expected, because adults are exposed to more seasonal influenza viruses and/or vaccines than young children, they have more complex antibody landscapes from past exposures through infection(s) and/or vaccination(s) with multiple influenza viruses (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Nowadays, antibody titers against PV1, MSLV and C. diphtheriae are required for IVIG batch release. [12] , [13] Otherwise evaluation must rely on the published literature, when available (WNV, 25 CMV, [26] , [27] , [28] ECHV, 16 HAV, [29] , [30] HBV, 30 IAV-IAB, [18] , [31] , [32] , [33] , [34] RUBV, [18] , [30] MSLV, [17] , [18] , [30] , [35] RSV, 34 VZV, [30] , [35] , [36] H. Influenzae , 37 C. tetani , [30] , [35] S. pneumoniae , 37 P. aeruginosa , 38 C. diphtheriae , [30] , [35] ).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased HAV antibody seroprevalence in Europe and the US has also been described, 29 which is in accordance with our results. Conversely, high titers against different subtypes of IAV (H5N1, 33 H2N2, 32 and H1N1, 31 ) and VZV 36 have been found in US IVIG preparations. In our study, IVIG samples from the US, together with Canada, showed the highest titer against IAV and VZV.…”
Section: Discussionmentioning
confidence: 99%
“…F10-like IgG Abs are also detected in pre-immune serum samples and increased significantly in H5N1 vaccinees. A low level of serum anti-HA Abs that bind and neutralize H5N1 viruses has been reported to be age and influenza exposure dependent [ 9 , 10 ]. Other investigators have reported enhanced levels of HA-directed anti-H5N1 neutralizing Abs in healthy donors after boosting with unrelated human influenza H1N1/H3N2 seasonal vaccines [ 5 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…To quantify the baseline levels of anti-influenza heterosubtypic Abs in human serum, we used IVIG as representative of pre-immune IgG Ab composition in the general population, which includes individuals who are likely exposed to seasonal influenza A virus infection and/or vaccinations (H1N1 and H3N2). Other investigators have shown that a low level of heterotypic anti-HA Abs that bind and neutralize H5N1 viruses is present in IVIG from diverse geographic locations [ 9 , 10 ]. These investigations further showed that these heterosubtypic anti-H5N1 Abs cross-react with H3N2 and H1N1; however, efforts to purify and characterize these Abs (beyond neutralization titers) have not been reported.…”
Section: Discussionmentioning
confidence: 99%